Production of silumins with highly dispersed inverted microstructure - E. I. Marukovich; V. Yu. Stetsenko (Литьë и металлургия, 2020)
Thermodynamic calculations of the structure of metal melts, processes of their crystallization and degassing in the eutectic reaction have been made. It is shown. That the main structural elements are nanocrystals, and hydrogen bubbles have a direct effect on the morphology of eutectic crystals and the phase structuring process. Physical and chemical principles and mechanisms for modifying the microstructure of silumins have been developed. It has been found that the main processes affecting the modification of phase crystals are the intensity of coagulation of nanocrystals, refining from adsorbed oxygen and hydrogen atoms, and preventing the release of hydrogen bubbles on eutectic crystals. Environmentally safe methods of casting silumins with highly dispersed inverted microstructure are developed, based on mixing of liquid metal and liquid-hard alloy, accelerated hardening and structural-hereditary modification. Antifriction silumin has been developed, which in terms of friction wear resistance exceeds and replaces industrial aluminium and tin bronzes, but is cheaper and lighter in 2–3 times. Universal silumin modifiers for steel, bronze, cast iron, brass have been developed. Devices and crystallizers with a flood-jet cooling system have been developed, which are 2–3 times more effective than normal ones. Experimental-industrial casting section for production of solid and hollow billets from silumins with highly dispersed inverted microstructure has been created. These pieces are supplied to more than 100 industrial enterprises of Belarus, Russia, Korea and Ukraine.